Workshop Program GIR (Get Into Rugby) Untuk Kelompok Kerja Guru (KKG) PJOK dan Musyawarah Guru Mata Pelajaran (MGMP) PJOK di Yogyakarta - Abdul Mahfudin Alim; Erlina Listyarini; Hendra Setyawan (Fakultas Ilmu Keolahragaan dan Kesehatan, Universitas Negeri Jakarta, 2023)
Invasion games is one of the classifications of sports games. Rugby is one of the sports games that is included in the invasion game classification. The sport of rugby can be played by anyone, but there are still many perceptions that rugby is only a sport that requires physical contact, so this sport is not yet popular among the public. This Community Service Program aims to provide basic knowledge about the sport of Rugby in the Special Region of Yogyakarta through the program Get Into Rugby (GIR). Community Service Program activities were carried out for one day, namely on Thursday, July 6 2023. The number of participants was 31 people, consisting of Physical Education teachers who were members of the Teacher Working Group and Subject Teachers' Conference (MGMP) of physical education in D.I. Yogyakarta. The activities ran smoothly without any significant obstacles. This community service implementation uses the workshop method with the aim of ensuring active participation from participants. The workshop began with a sharing session in the classroom and practice in the field. Each participant is given the opportunity to demonstrate a basic teaching or coaching training session model best practice World Rugby standards. In the activity process, it was seen that the participants were active and enthusiastic about participating in the activity. Quantitative data shows that there is a significant increase in understanding of the basic knowledge of the game of Rugby based on the results of the pretest and posttest where it was obtained -t count < - t table (-12.129 <-1.697). Qualitative data shows that there was a change in initial perception and after participating in the GIR workshop activities where it was stated that Rugby was a sport that was fun and could be played by all groups, body shape and gender where the initial perception before participating in GIR activities was that they had the perception that Rugby was a hard sport that required conditions. physical and can only be played by certain groups.